The world almanac and book of facts, 2009 - Joyce, C. Alan. (New York : World Almanac, 2009)
Contains thousands of facts and statistics on a variety of subjects, such as science, economics, sports, arts, and media; and includes information on the 2008 Beijing Olympics and presidential election.
Includes indexes.
Young Adult
Keywords: Almanacs; Statistics; Statistics